Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0190777
|View full text |Cite
|
Sign up to set email alerts
|

Invasion strategies in round goby (Neogobius melanostomus): Is bigger really better?

Abstract: Few studies have systematically investigated mid- or long-term temporal changes of biological characteristics in invasive alien species considering the different phases of an invasion. We studied the invasion performance of one of the most invasive species worldwide, the round goby Neogobius melanostomus, from total absence over first occurrence until establishment from 2010 to 2015 in the upper Danube River. After an upstream movement of the invasion front of about 30 river km within four years, the pattern t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 78 publications
(141 reference statements)
4
19
0
Order By: Relevance
“…Indeed, Hohenadler et al [15] has shown that P. laevis is in the process of replacing the endemic P. tereticollis in eels captured from the High Rhine. However, the gobies did not passed the Rhine Falls to reach the Bodensee area and have also not spread into the river Danube in Baden-Württemberg [37,52]. This is consistent with the front of the expansion of P. laevis over the Danube not reaching Austria yet in 2006 [18] and our finding that Graylings from the Danube River being infected with P. tereticollis rather than P. laevis.…”
Section: Plos Onesupporting
confidence: 75%
“…Indeed, Hohenadler et al [15] has shown that P. laevis is in the process of replacing the endemic P. tereticollis in eels captured from the High Rhine. However, the gobies did not passed the Rhine Falls to reach the Bodensee area and have also not spread into the river Danube in Baden-Württemberg [37,52]. This is consistent with the front of the expansion of P. laevis over the Danube not reaching Austria yet in 2006 [18] and our finding that Graylings from the Danube River being infected with P. tereticollis rather than P. laevis.…”
Section: Plos Onesupporting
confidence: 75%
“…In N . melanostomus it was found that individuals at the invasion front were different from those in longer established areas, mostly in traits related to size, growth, and feeding (the “bigger is better” hypothesis), increasing their competitive capability [ 57 , 58 ]. Therefore incorporating intra-specific variation in ecomorphological analyses to assess invasion risk is highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The higher activity of males can be a reason why there is a higher proportion of males in some newly invaded sites (Azour et al ., ; Gutowsky & Fox, ). On the other hand, some studies observed the opposite sex ratios at invasion fronts (Brandner et al ., a, ; Gutowsky & Fox, ). Such discrepancy could be related to population‐specific reactions to various ecological conditions or different sampling methods.…”
Section: Comparisons Of Activity‐selective Gillnets and Activity Non‐mentioning
confidence: 99%
“…The higher activity of males can be a reason why there is a higher proportion of males in some newly invaded sites (Azour et al, 2015;Gutowsky & Fox, 2011). On the other hand, some studies observed the opposite sex ratios at invasion fronts (Brandner et al, 2013a(Brandner et al, , 2018Gutowsky & Fox, 2012).…”
mentioning
confidence: 99%